Upaya Guru Dalam Meningkatkan Budaya Literasi Siswa Di MI Ma'arif NU Manbaur Rohmah Gresik - Febrina Inka Nur Azizah; Ismail Marzuki (Departement of Mathematics Education, 2023)
This study aims to determine literacy activities, obstacles, and efforts made by schools in increasing elementary school students' interest in reading. This study used a descriptive qualitative method with interview and observation data collection techniques. The results of the study show that 2 factors influence literacy culture, namely inhibiting factors and supporting factors. Inhibiting factors include students' lack of interest in reading, the influence of gadgets due to increasingly sophisticated technological developments, lack of awareness from students, and lack of parental involvement in literacy activities. Supporting factors from parents, teachers, and facilities and infrastructure. Efforts made by the teacher in improving literacy culture are making class libraries or reading corners, moving class activities used for literacy once a week, muhadhoro activities which are carried out once a month on the last Friday of the week where children display creations such as speeches and sholawat, Providing tiered pin rewards starting from beetle pins to lions, Providing a representative library and providing 70% fiction books (story books) and 30% non-fiction books.